(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The article explores ways to enhance the effectiveness of an indicator-based management system in pedagogical higher education institutions. The research process includes theoretical, analytical, and empirical stages. It is shown that management processes can be optimized, education quality improved, and resources used efficiently through indicators.